On the issue of mistakes' diagnostics for recognizing and understanding compound words - Velička, A.; Križinauskas, J. (Psichologija, 1977)
Many unknown words in the text factor is one of the factors interfering with the synthetic comprehension of the text. When starting to prepare exercises that form the ability and skills to understand unknown words by reading a text, a pedagogical-diagnostic study was performed at the Vilnius Institute of Engineering. The results showed that errors in the comprehension of compound words in German are explained either by language difficulties or by mental activity in perceiving, recognizing, and understanding compound words. Students do not know the most commonly used word formation models, do not have the skills to analyze the structure of words. Mistakes can be avoided by systematically performing targeted word-making exercises.
Keywords: diagnostics; compound words